Diss rates sensitivity analysis.xlsx - Gutierrez-Carazo, Encina (Cranfield University, 2022)
Sensitivity analysis to asses the effect of temperature and water pH on the dissolution and breakthrough of IHE comounds in soil Simulations were performed in GoldSim and experimental work in the laboratory.
Keywords: 'Statistics'; 'sensitivity analysis'; 'soil science'